PEMBUATAN FILM DOKUMENTER TENTANG HAJI DAVID UMAR - EDO ADRIAN, Drs. Syafwandi, M.Sn., Dra. Zubaidah, M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2016)
David Haji Umar Umar or familiarly called by Haji Id is a successful entrepreneur and successful in the field of culinary named Cafe Batang Agam in Payakumbuh. Haji Id have a hard life experience in the past. Travel and life experiences of the implementation until now and is often used as an example by the public as a lesson in life. Haji Id is a figure that persistent, motivated and hardworking. Viewed from the persistence and hard work that is owned by him, came the idea to make a documentary. The goal is to demonstrate to the public about the life of Haji Id and demonstrate to the public that with hard work and perseverance in carrying something that is impossible to do. In addition, through this documentary is also expected to promoting Cafe Batang Agam Haji Id.This thesis aims to produce a documentary about Haji Id. The design method used by the authors is the beginning of a method of collecting data through observation, interviews, and documentation. Then proceed with the data analysis method using data analysis 5W-1H (What, Where, When, Who, Why and How), then concludes the analysis of data and perform a creative approach (the main media and supporters). In making this documentary writer and visual displays verbal message for the audience to see / watch this movie.With the making of a documentary about Haji Id, is expected to increase the motivation of people to work harder in life. In addition, is expected to attract the attention of buyers or the public at large so as to enhance the efforts of existence culinary field named Cafe Batang Agam in Payakumbuh this.Key word: Film Documentar, Haji ID, Desain.